After School Academy Foundation - SEPULVEDA, FELIX (2019)
Executive summary. After School Academy (A.S.A.) is created to deliver an innovative alternative as a pedagogical-technical private support (ATE) in Chile, permitting to connect own founder’s academic experience, skills and passion with an existing gap related to a Chilean education grant supporting vulnerable students, which regarding OECD, is not being used effectively. To change this, skilled professionals, national and international partners will improve current schools’ educational plans with services focused on two pillars called: Integral support and innovative football drills. Both aims to rise students’ motivation and aspirations resulting in students’ academic performance improvements. A.S.A.'s projections indicate revenue might increase from 10K in 2020 to 41k in 2023 due to a probable rise in the number of service contract with school providers. Team management expects to donate 3.5k and achieve company sponsorship of 5k annually and also personal sponsorship with annual targets. Its net profit margin is 35% in 2020 decreasing then due to major overheads to achieve preparedness for expansion. Cash flow forecast presents further capital expenditure with the same objective. Its break-even point is reached delivering four contracts per year which happens during the second-year operating. As foundation located in the second largest city in Chile (8th region), it will work closely with schools and its students. It will be financed by its Founder and Finance manager and overseen by its Communication and excellence manager and Head of operations. Together they have worked on the next developments.  It is part of the ATE certification process, currently being reviewed by the Chile’s Ministry of Education.  Appointment booked with CFO of one of the most active Chilean family office to achieve first sponsorship.  Appointment booked with DEM Director to present After School Academy.  Appointment booked in December with Carlos Saavedra Rubilar, University of Concepcion’s chancellor, to present him After School Academy.  Being guided by Jack Kavanagh, Sport Volunteer Officer at UoN to obtain support by Laureus Sport for Good.